Whence and Whither the Convolvulus Psyllid? An Invasive Plant Leads to Diet and Range Expansion by a Native Insect Herbivore. (25th February 2019) - Horton, David R; Kaur, Navneet; Cooper, W Rodney; Miliczky, Eugene; Badillo-Vargas, Ismael E; Esparza-Díaz, Gabriella; Rashed, Arash; Waters, Timothy D; Wohleb, Carrie H; Johnson, Daniel L; Kawchuk, Lawrence; Jensen, Andy S
Abstract: Arrival and spread of nonnative plant species can lead to changes in structure and function of the native insect fauna that include shifts in host use by native insect herbivores. Well-documented examples showing that these host shifts also lead to range expansion of native herbivores are, however, surprisingly rare. Evidence for range expansion requires an understanding of the insect's distribution preceding arrival of exotic species. These data often are lacking. The North American psyllid Bactericera maculipennis (Crawford) (Hemiptera: Triozidae), a specialist herbivore on plants in the Convolvulaceae, has been hypothesized to have expanded its geographic range after colonizing the exotic field bindweed ( Convolvulus arvensis L.; Convolvulaceae ). Efforts to test this idea run into the same retrospective problems typical of these analyses, in that the psyllid's host plant and its geographic distribution preceding arrival of C. arvensis are uncertain. We used the psyllid's current association with C. arvensis to help identify its natal (pre-bindweed) host, reasoning that a host shift by this specialist herbivore would be more likely if natal and exotic species are closely related. Phylogenetic analyses of plants, rearing trials, and field records led us to target species of Calystegia R. Brown (hedge and false bindweeds; Convolvulaceae) as natal hosts of B. maculipennis . The current presence of B. maculipennis in regions lacking Calystegia but where C. arvensis is common supported the hypothesis that arrival of the exotic weed C. arvensis has indeed led to range expansion by this host-specialized psyllid.